Wall Street and the Housing Bubble - Cheng, Ing-Haw; Raina, Sahil; Xiong, Wei (American Economic Review, 2014)
We analyze whether midlevel managers in securitized finance were aware of a large-scale housing bubble and a looming crisis in 2004–2006 using their personal home transaction data. We find that the average person in our sample neither timed the market nor were cautious in their home transactions, and did not exhibit awareness of problems in overall housing markets. Certain groups of securitization agents were particularly aggressive in increasing their exposure to housing during this period, suggesting the need to expand the incentives-based view of the crisis to incorporate a role for beliefs. (JEL D14, D83, E32, E44, G01, G21, R31)